From Retail to Grocery: Money Politics in 2014 Indonesian Legislative Election - Aminuddin, M. Faishal; Attamimi, Natasha Hassan (Political Science Program, Universitas Negeri Semarang, 2019)
Money politics is a serious problem for the improvement in the quality of democracy in Indonesia. In every election, there has been a shift or variation in the pattern of money politics. This article answers the important question of what pattern of money politics applied in the 2014 elections was. This study found that the pattern was more complex and that it involved more actors between not only candidates and voters, but also the election organizers. A case study had been used to view the pattern of money politics in the legislative elections in Surabaya and Sidoarjo during the 2014 election. This study explains the connectivity between the emergence of pragmatic-rational voters, the engagement of the party oligarchy in moving the political party machinery and the covert dealings with the election organizer.